PENERAPAN METODE MULTILEVEL FEEDBACK QUEUE PADA SISTEM INFORMASI PEMESANAN PAKET HAJI DAN UMRAH DI PT.AUBAINE KABUHAYAN - Muhammad Arif Suhada; Ilka Zufria; Ali Ikhwan (UIN Sumatera Utara Medan, 2020)
Hajj and umrah is a visit to Mecca to implement the 5th pillar of Islam which is required for Muslims in carrying out it, especially for those who are able to carry it out. With the technology that has been developed at this time the Hajj and Umrah package ordering information system is urgently needed in an effort to improve services to people who will perform Hajj or Umrah, by allowing each pilgrim to use the system that has been provided for ordering Hajj and Umrah packages. Multilevel feedback queue is an algorithm based on a queuing system which can provide recommendations based on the priority of prospective pilgrims who have registered by making several criteria as a support in determining the highest priority to the lowest, this algorithm is very possible to move queues in accordance with specified priorities by pilgrims and umrah.Keywords: Hajj and Umrah, Queue Information System and Multilevel Feedback